Planetary health in action: developing a heatwave vulnerability tool for primary care - Karolina Griffiths; Paul Basso-Bert; Mireille Abraham; Elise Chin; Layana Caroupaye-Caroupin; Manal Ahikki; Emilie Agrech; Camille Debrock; Rim Sabri; Grégoire Mercier; François Carbonnel (BJGP Open)
Background: Heatwaves are becoming longer and more frequent. Despite the availability of open environmental data, little is operable and formatted for primary care use. Aim: To create a user-friendly online mapping tool to assess the vulnerability of communities to heatwaves for use by primary care practitioners. This study questioned what knowledge needed to be deployed, who needed to participate, and how the knowledge should be shared. Design & setting: A participatory action-research project based on knowledge mobilisation (KM) in France, as part of the Green Data for Health Challenge. Method: Knowledge was summarised on the factors most affecting heatwave vulnerability in a collaborative process, enabling a consensus on data variables and mobilised content for the online tool. Purposive sampling included primary care stakeholders with Regional Health Agencies (Agence Régionale de Santé; ARS), Public Health France (Santé Publique France; SPF), and data scientists. Results: Nineteen participants took part in 10 co-construction meetings, a brainstorming carousel strategy, and five weekly co-creation meetings between December 2022 and June 2023. The heatwave vulnerability variable was constructed using surface temperature, social deprivation, vegetation coverage, and presence of air-conditioning equipment. Identified experts mobilised data on the national composite indicator at the communal level for heatwave morbidity. Conclusion: There is no standard platform for sharing environmental data in France. This co-creation study offers a new approach to incorporating environmental data on heatwaves into primary care consultations. We demonstrate the importance of KM in primary care to bridge the research–practice gap. Integrating primary care records with environmental data may promote broader applications for planetary health research.